Multiscale Thermo-Dynamics : Introduction to GENERIC - Pavelka, Michal; Grmela, Miroslav; Klika, Václav (De Gruyter, 2018)
One common feature of new emerging technologies is the fusion of the very small (nano) scale and the large scale engineering. The classical environment provided by single scale theories, as for instance by the classical hydrodynamics, is not anymore satisfactory. The main challenge is to keep the important details while still be able to keep the overall picture and simplicity. It is the thermodynamics that addresses this challenge. Our main reason for writing this book is to explain such general viewpoint of thermodynamics and to illustrate it on a very wide range of examples. ContentsLevels of descriptionHamiltonian mechanicsIrreversible evolutionReversible and irreversible evolutionMulticomponent systemsContact geometryAppendix: Mathematical aspects